2016
DOI: 10.1038/srep38014
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase gp91phox contributes to RANKL-induced osteoclast differentiation by upregulating NFATc1

Abstract: Bone-marrow derived monocyte-macrophages (BMMs) differentiate into osteoclasts by M-CSF along subsequent RANKL stimulation possibly in collaboration with many other unknown cytokines released by pre- or mature osteoblasts. The differentiation process requires receptor activator of nuclear factor kappa-B ligand (RANKL)/RANK signaling and reactive oxygen species (ROS) such as superoxide anion (O2•−). Gp91phox, a plasma membrane subunit of NADPH oxidase (Nox), is constitutively expressed in BMMs and plays a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 46 publications
0
45
0
Order By: Relevance
“…Recent studies revealed that a multicomponent phagocyte‐type NADPH oxidase is a major source of ROS production in many non‐phagocytic cells including renal mesangial cells . Gp91‐phox is a core regulatory subunit of NADPH oxidase . It is reported that when the balance between the anti‐oxidative and oxidative status was broken by oxygen, large numbers of ROS may activate mitochondrial stress pathways to cause mitochondrial injury .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies revealed that a multicomponent phagocyte‐type NADPH oxidase is a major source of ROS production in many non‐phagocytic cells including renal mesangial cells . Gp91‐phox is a core regulatory subunit of NADPH oxidase . It is reported that when the balance between the anti‐oxidative and oxidative status was broken by oxygen, large numbers of ROS may activate mitochondrial stress pathways to cause mitochondrial injury .…”
Section: Discussionmentioning
confidence: 99%
“…29 Gp91-phox is a core regulatory subunit of NADPH oxidase. 30 It is reported that when the balance between the anti-oxidative and oxidative status was broken by oxygen, large numbers of ROS may activate mitochondrial stress pathways to cause mitochondrial injury. 31 protease activating factor 1, resulting in the production of apoptotic body.…”
Section: Co-culture Of Gdnf-afscs Restrained H/r-induced Mrtecs Apomentioning
confidence: 99%
“…The NOX plasma membrane subunit Gp91 phox is important for osteoclast differentiation since it induces NFATc1, a downstream signaling mediator of RANK (Kang and Kim, 2016). NFATc1, the master switch for regulating osteoclast differentiation, binds directly to the promoter region of fusion-mediating molecules gene as Dcstamp .…”
Section: Discussionmentioning
confidence: 99%
“…Female p47 phoxÀ/À (part of NOX isoform 2) mice are protected from alcohol-induced bone resorption (Mercer et al, 2014). In a recent work, gp91 phoxÀ/À mice exhibited protected expression of transcription factors responsible for osteoclast formation, including nuclear factor of activated T-cells cytoplasmic 1 (NFATc1) and NF-kB (Kang and Kim, 2016). In a recent work, gp91 phoxÀ/À mice exhibited protected expression of transcription factors responsible for osteoclast formation, including nuclear factor of activated T-cells cytoplasmic 1 (NFATc1) and NF-kB (Kang and Kim, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation